Biomass Valorization to Produce Porous Carbons: Applications in CO2 Capture and Biogas Upgrading to Biomethane—A Mini-Review - Bernardo, Maria; Lapa, Nuno; Fonseca, Isabel; Esteves, Isabel A. A. C. (Frontiers in Energy Research, 2021)
Porous carbon materials, derived from biomass wastes and/or as by-products, are considered versatile, economical and environmentally sustainable. Recently, their high adsorption capacity has led to an increased interest in several environmental applications related to separation/purification both in liquid- and gas-phases. Specifically, their use in carbon dioxide (CO2) capture/sequestration has been a hot topic in the framework of gas adsorption applications. Cost effective biomass porous carbons with enhanced textural properties and high CO2 uptakes present themselves as attractive alternative adsorbents with potential to be used in CO2 capture/separation, apart from zeolites, commercial activated carbons and metal-organic frameworks (MOFs). The renewable and sustainable character of the precursor of these bioadsorbents must be highlighted in the context of a circular-economy and emergent renewable energy market to reach the EU climate and energy goals. This mini-review summarizes the current understandings and discussions about the development of porous carbons derived from bio-wastes, focusing their application to capture CO2 and upgrade biogas to biomethane by adsorption-based processes. Biogas is composed by 55–65 v/v% of methane (CH4) mainly in 35–45 v/v% of CO2. The biogas upgraded to bio-CH4 (97%v/v) through an adsorption process yields after proper conditioning to high quality biomethane and replaces natural gas of fossil source. The circular-economy impact of bio-CH4 production is further enhanced by the use of biomass-derived porous carbons employed in the production process.